Clinical accompaniment: the critical care nursing students' experiences in a private hospital - N. Tsele; Marie Muller (AOSIS, 2000)
The quality of clinical accompaniment of the student enrolled for the post-basic diploma in Medical and Surgical Nursing Science: Critical Care Nursing (General) is an important dimension of the educational/learning programme. The clinical accompanist/mentor is responsible for ensuring the student's compliance with the clinical outcomes of the programme in accordance with the requirements laid down by the Nursing Education Institution and the South African Nursing Council. The purpose of this study was to explore and describe the experiences of the students enrolled for a post-basic diploma in Medical and Surgical Nursing Science: Critical Care Nursing (General), in relation to the clinical accompaniment in a private hospital in Gauteng. An exploratory, descriptive and phenomenological research design was utilised and individual interviews were conducted with the ten students in the research hospital. A content analysis was conducted and the results revealed both positive and negative experiences by the students in the internal and external worlds. The recommendations include the formulation of standards for clinical accompaniment of students. the evaluation of the quality of clinical accompaniment of students and empowerment of the organisation, clinical accompanists/mentors and clinicians.